E Estetika Film Pendek: Estetika Film Pendek - Arda Muhlisiun Muhlisiun; RB Armantono; Subagjo Budisantoso (PANGGUNG, 2026)
This study analyzes short films, which are understood not as a condensed form of feature-length films, but as a cinematic form with its own distinct aesthetic, characterized by narrative density and stylistic precision. Through a literature review of narrative theory and film style, literature on short films, semiotics, and studies of Indonesian short films, this research demonstrates that the aesthetics of short films are constructed through the way the narrative selects the most decisive events and scenes: a single conflict, economical dialogue, gestures, objects, space, music, and image composition. Film style reinforces the narrative through the selection of shots, framing, lighting, editing, acting, and sound design, which shape the atmosphere, intimacy, and emotional tension. All these elements function as signifiers that evoke value and meaning in the name of short film aesthetics. Thus, the aesthetics of short films lie in their ability to present a tightly structured narrative, using both symbolic and functional cinematic techniques, making them effective as a medium for education, cultural representation, social critique, and artistic expression.